2023
DOI: 10.3390/diagnostics13223437
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Emotional and Immersive Outcomes in the Context of Virtual Reality Scene Interactions

Yaşar Daşdemir

Abstract: The constantly evolving technological landscape of the Metaverse has introduced a significant concern: cybersickness (CS). There is growing academic interest in detecting and mitigating these adverse effects within virtual environments (VEs). However, the development of effective methodologies in this field has been hindered by the lack of sufficient benchmark datasets. In pursuit of this objective, we meticulously compiled a comprehensive dataset by analyzing the impact of virtual reality (VR) environments on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…The researchers concluded that while various models for detecting cybersickness have been developed, there is no model to predict early adverse events in VEs. Future, more accurate and effective ML approaches will undoubtedly be inspired by current knowledge of how the brain works, as well as the new brain/organism models/approaches being developed and linking them to these bio-digital frontiers ( Benelli et al, 2023 ; Daşdemir, 2023 ; Yang et al, 2023 ). These and similar studies ( Chang et al, 2023 ; Souchet et al, 2023 ) indicate, as does our research, that we are still at the beginning of understanding the potentially beneficial and detrimental effects of digital worlds on their users, especially older adults ( Drazich et al, 2023 ; Séba et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers concluded that while various models for detecting cybersickness have been developed, there is no model to predict early adverse events in VEs. Future, more accurate and effective ML approaches will undoubtedly be inspired by current knowledge of how the brain works, as well as the new brain/organism models/approaches being developed and linking them to these bio-digital frontiers ( Benelli et al, 2023 ; Daşdemir, 2023 ; Yang et al, 2023 ). These and similar studies ( Chang et al, 2023 ; Souchet et al, 2023 ) indicate, as does our research, that we are still at the beginning of understanding the potentially beneficial and detrimental effects of digital worlds on their users, especially older adults ( Drazich et al, 2023 ; Séba et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%